2019
DOI: 10.1155/2019/4547632
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Model Updating of Satellite Sailboard Based on Sensitivity Analysis

Abstract: The modal analysis of a satellite sailboard finite element model is carried out to accurately investigate the response of a satellite sailboard in a complex loaded space environment through simulation. The basic excitation vibration test of the satellite sailboard is used to perform model matching and a correlation test. Appropriate design variables are selected through sensitivity analysis. Modal analysis data and vibration table excitation test response data are used to modify the finite element model. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Luo et al performed FEM model matching of the satellite sailboard based on sensitivity analysis. e low-order frequency errors in the simulation model were less than 5%, and the high-order errors were less than 10% [17]. For the solar array of multiple plates, the parameter number is large, while the accuracy of the FEM model is insufficient.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Luo et al performed FEM model matching of the satellite sailboard based on sensitivity analysis. e low-order frequency errors in the simulation model were less than 5%, and the high-order errors were less than 10% [17]. For the solar array of multiple plates, the parameter number is large, while the accuracy of the FEM model is insufficient.…”
Section: Introductionmentioning
confidence: 91%
“…erefore, it is necessary to combine the second type of method, that is, the correction of the systematic errors. Usually, a finite element model for model updating or a theoretical model for error estimation is established [14,15]. e accurate parameters in models are obtained by a series of tests.…”
Section: Introductionmentioning
confidence: 99%
“…They assessed that updated FEM's were efficient enough to analyze the dynamic characteristics of the honeycomb sandwich plate. Recently, Luo et al 22 introduced the FEM updating of a satellite honeycomb sandwich sailboard. They selected appropriate design variables based upon sensitivity analysis results.…”
Section: Introductionmentioning
confidence: 99%
“…Since the honeycomb core sandwich structures have been widely used in the aerospace industry, especially in the satellite structure, some studies have focused on the vibration of the satellite structure by applying the FE method. [21][22][23][24][25][26][27][28][29][30] For example, Bai et al 22 analyzed the theory of normal modes of satellite with honeycomb sandwich plate structure using the commercial finite element PATRAN/NASTRAN software, where they performed the modal analysis of the satellite according to the equivalent model. They found that the FE method is an applicable modal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al 24 compared the three sandwich, equivalent-plate, and honeycomb-plate theories, to identify the equivalent parameters of the honeycomb sandwich plates, found that the honeycomb-plate theory is the most appropriate in simplifying the spacecraft structure. Luo et al 27 carried out the modal analysis of a satellite sailboard in a complex loaded space environment through simulation. In order to validate the results of the finite element model, they used the basic excitation vibration test of the satellite sailboard.…”
Section: Introductionmentioning
confidence: 99%